Reliability and Validity of WOTA 1 & 2 Water Assessment Tests Based on the Halliwick Concept in Children with Cerebral Palsy - Chandolias Κωνσταντίνος; Tsiokanos Αθανάσιος; Konstantinidou Ελισάβετ - Ανδριάνα; Tsimeas Παναγιώτης (Inquiries in Physical Education and Sport, 2019)
The Water Orientation Tests of Alyn 1 and 2 (WOTA 1 & 2) have been developed by the need to create specific assessment tests in the aquatic environment based on the Halliwick therapeutic bathing concept. The purpose of this study was to investigate the validity and reliability of the two aquatic functional assessment tests (WO-TA1, WOTA2) for evaluating adjustment and functional ability in the aquatic environment of people with disabilities. Forty children with cerebral palsy of 2.4 - 13.8 years participated in the study. Twenty of them with GMFCS 1-5 and cognitive limitations participated in the WOTA 1 study, and twenty children with GMFCS 1-4 without cognitive limitations participated in the WOTA 2 study. The results showed that the test-retest and inter-rater reliability for the overall score was excellent for both WOTA 1 (ICC = 0.993) and WOTA 2 (ICC = 0.997). In terms of validity, a positive correlation was found between WOTA 1 and GMFM (r = 0.63) and WOTA 2 and GMFM (r = 0.58). The conclusion is that both evaluation tests are valid and highly reliable for assessing mental adjustment and function in the aquatic environment for children with disabilities.